Cardiac Work-Up Protocol for Liver Transplant Candidates: Experience from a Single Liver Transplant Centre. (2012) - Ye, Carrie; Saincher, Meghana; Tandon, Puneeta; Meeberg, Glenda; Williams, Randy; Burak, Kelly W; Bain, Vincent G
Abstract : BACKGROUND: Ischemic cardiac events can cause significant morbidity and mortality postliver transplantation; however, no validated protocols to screen patients before transplantation exist. OBJECTIVES: To report the introduction of a noninvasive cardiac screening protocol used at the Liver Unit, University of Calgary (Calgary, Alberta); to determine whether the protocol decreases use of coronary angiograms; and to compare cardiac outcomes using the new protocol with an appropriately matched historical control group. METHODS: A new cardiac screening protocol was introduced into the program in 2005, which uses perfusion scintigraphy to screen high-risk cardiac patients, reserving coronary angiograms for abnormal results. Transplanted patients screened using this protocol were compared with matched historical controls. Electronic charts were reviewed for cardiac outcomes intra- and postliver transplantation. RESULTS: A total of 396 patients were screened between April 2005 and February 2009. Eighty-two were transplanted by February 2009 and included in the study. Eighty-one patients were successfully matched according to age, sex, cardiac history and presence of diabetes. Twelve of 82 (14.6%) and 11 of 81 (13.6%) in the study and control groups, respectively, underwent coronary angiograms (P=0.85). Coronary artery disease was found in six of 12 (50.0%) study patients and three of 11 (27.3%) control patients who underwent coronary angiography (P=0.27). The mean (± SD) length of the follow-up period was 1.87±0.91 years and 4.45±1.89 years in the study and control groups, respectively. One of 81 in the control group and zero of 82 in the study group experienced an acute coronary syndrome event postoperatively. CONCLUSIONS: Coronary events are infrequent in liver transplant recipients. The described protocol is an effective method of coronary artery disease screening before liver transplant but does not reduce the number of cardiac investigations performed.